Skorsing dan Sanksi Administratif Bagi Prajurit TNI Bagi Prajurit yang Melakukan Pelanggaran Hukum - Arief Fahmi Lubis (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2021)
The provision of suspensions and administrative sanctions is intended as an effort to develop personnel and provide a deterrent effect for law violators, and to prevent other TNI soldiers from imitating them. The aim of this research is to show that TNI soldiers are different from civilians who are only bound by general legal rules, TNI soldiers are not only bound by general legal rules but also bound by military legal rules (military disciplinary law and military criminal law), so it can be said that it is not easy. for a TNI soldier when faced with the implementation of legal regulations. Qualitative research uses a descriptive approach to collect data systematically, factually and quickly according to the description at the time of the research. The results of this research show that TNI soldiers who violate the law are subject to suspension and administrative sanctions are two things that are closely related to the legal process and personnel development. This condition causes special burdens for a TNI soldier who violates the law because it impacts his career and income.